Restoration of obliterated stamped marks on cast iron surfaces by etching techniques - Abdul Wahab, Mohd Farizon (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Restoration of erased obliterated marks on cast iron surface by chemical etching is very difficult. Hence, a series of experiments were conducted to identify a sensitive and efficacious reagent that could recover obliterated stamped numbers on this surface. One cast iron (3.29%C) car engine block was purchased and cut into several small pieces. Some numerical characters were stamped on their surfaces using Instron Table Mounted Universal Testing Machine at 8kN. The stamped numbers were then removed by filing until no longer visible. Eight metallographic of which most contained copper compounds were chosen for restoration. The restoration was done by swabbing and immersion techniques. The results have shown that among eight etching reagents a modified Fry's reagent consisting of 45 gram cupric chloride, I OOmL hydrochloric acid, and 180mL water gave excellent contrast and sensitivity of the recovered numbers. This reagent also successfully recovered the marks obliterated by centre punching/peening and over stamping. liPage